The Development Analysis of Ability Memorizing in Qur'an on Early Childhood at PAUD Bait Qurany Saleh Rahmany, Banda Aceh, Indonesia - Dahliani Dahliani; Anita Yus; Masganti Sitorus (Budapest International Research and Critics University, 2019)
This study aims to: (1) Analyze the implementation of learning to memorize the Qur'an in early childhood, (2) Analyze the ability to memorize the Qur'an in early childhood, (3) Describe the supporting factors and (4) describe the factors inhibitors of memorizing the Qur'an in early childhood in PAUD Bait Qurany Saleh Rahmany. Research using qualitative descriptive methods. Data collection techniques used in this study were: interviews, observation and documentation. Data analysis in this study uses the interaction model of Miles and Huberman, with steps : data reduction, data presentation, conclusion drawing or verification. The results showed that: (1) the implementation of learning to memorize the Qur'an in early childhood is done by using the talqin method, memorization techniques with Jarimatika formula, with visual, audio and kinesthetic patterns, (2) the ability to memorize the Qur'an ' in children, namely the ability of natural talent that is trained repeatedly and optimally until it becomes an achievement, (3) supporting factors in memorizing the Qur'an, namely parent support, interests and talents, and adequate school facilities, (4) factors inhibitors in memorization are the internal factors of the child and the external factors of the child. The results of the research are recommended to be applied in all Paud based on qur'an tahfiz by collaborating on the national curriculum and school-specific curriculum.